Análise de um sistema de aquecimento solar caseiro para residências do interior do Rio Grande do Norte - Silva, Layane Araújo (Universidade Federal Rural do Semi-Árido, 2020)
In view of the high and increasing consumption of electricity in the residential sectors of the country, especially with regard to the use of electricity in water heating for bathing, such questions arise: The use of solar energy, as an alternative energy source for heating water , will you be able to collaborate with the electric energy saving in semi-arid regions of northeastern Brazil, where the use of the electric shower is made on a smaller scale, and because these regions have, in their majority, less significant drops in temperature at night? Would it be feasible to implement a thermosyphon system, where it is not necessary to use a pump to circulate the water? This work will address these issues, by investigating factors that influence the feasibility of implementing a low-cost Solar Heating System (SAS) for a residence located in the semi-arid region of Rio Grande do Norte. To this end, the construction of the residential and hydraulic project for a residence located in the municipality of Angicos / RN was developed, using the REVIT software, and later, a project for the home heater reservoir, which incorporates the low-cost solar collector. In view of what has been accomplished, it was found that the implementation of low-cost SAS in the Angolan municipality tends to be satisfactory, even in view of the semi-arid characteristics, considering that the system would allow savings in financial expenses with electricity and would allow the heating of the water would become accessible to low-income families.
Analysis of a homemade solar heating system for interior residences in Rio Grande do Norte
Artigo
Keywords: Aquecedor solar; Baixo custo; Energia renovável; Solar heater; Low Cost; Renewable energy; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA